An adsorption–reduction synergistic effect of mesoporous Fe/SiO2–NH2 hollow spheres for the removal of Cr(vi) ions. Issue 32 (14th March 2016) - Yao, Honglin; Ding, Qianqian; Zhou, Hongjian; Zhao, Zhenfu; Liu, Gang; Wang, Guozhong
Abstract : Mesoporous Fe/SiO2 –NH2 hollow spheres were successfully prepared as a magnetic absorbent for the highly effective removal of Cr(vi ) ions through an adsorption–reduction synergistic effect. Abstract : In this study, mesoporous amino-group functionalised iron/silica hollow spheres (Fe/SiO2 –NH2 HSs) were successfully developed as a magnetic absorbent for the highly effective removal of Cr(vi ) ions. The Fe/SiO2 –NH2 HSs were synthesized using monodispersed silica colloids as a chemical template, followed by a one-pot hydrothermal treatment, hydrogen reduction and surface modification with an amino silane coupling agent. The Fe/SiO2 –NH2 HSs have a diameter of ca. 950 nm and a shell thickness of ca. 60 nm, and the surfaces were composed of Fe and SiO2 units with amino functional groups. Meanwhile, the ferromagnetic property endowed them with easy recyclability for practical applications. The Fe/SiO2 –NH2 HSs exhibited significantly improved ability to remove pollutant Cr(vi ) and methyl orange. The removal percentage of Cr(vi ) (8 mg L −1 ) could reach 98.3% in just 5 min using Fe/SiO2 –NH2 HSs; however, only 10% of Cr(vi ) were removed using the unmodified samples. XPS analysis suggested that the removal of Cr(vi ) was attributed to the adsorption and reduction synergistic process of the Fe/SiO2 –NH2 HSs. During the process, an electrostatic attraction occurred between the positively charged amino-groups and the negatively charged pollutant species in the aqueous solution, and adsorbed Cr(vi ) ions were reduced to Cr(iii ) species by the iron of Fe/SiO2 –NH2 HSs.